Respuesta :

Answer:

D: c=(ab-d)/a

Step-by-step explanation:

a(b-c)=d

ab-ac=d

ab=ac+d

ab-d=ac

(ab-d)/a=c

D. c=ab-d/a is the correct answer.  First you had to add by -ab from both sides of equation, and it gave us, [tex]ab-ac+-ab=d+-ab[/tex], or [tex]-ac=-ab+d[/tex]. Then divide by -a from both sides of equation, and it gave us, [tex]\frac{-ac}{-a}= \frac{-ab+d}{-a}[/tex], and it gave us the answer is c=ab-d/a is the right answer.  Hope this helps! And thank you for posting your question at here on brainly, and have a great day. -Charlie

ACCESS MORE